Planta desalinizadora de agua como alternativa de emergencia en instituciones educativas de la Guajira, Colombia (2023)
The supply of drinking water is a global challenge, especially in coastal regions such as La Guajira, where water scarcity is a constant problem that affects children and young people, limiting schools in the region from providing basic hygiene and food services, resulting in the majority of cases in the absence of students in educational institutions, then to address the water scarcity problem, new technologies have been implemented to harness nearby water resources. However, many of these technologies are expensive and difficult to implement, necessitating more efficient and cost-effective alternative solutions. This paper presents the development of a seawater desalination plant as an emergency alternative for obtaining drinking water from seawater. The solar desalination system consists of three subsystems that contribute to the efficiency of the process: a heat exchanger system, which accelerates the cooling process of the distilled water vapor to obtain a higher liquid flow; a fluid distribution system, and a level control system, which maintain the appropriate water level in the reactor to optimize the production of distilled water. This system aims to produce a maximum of 1300 liters of water per day for common uses, making it an efficient and economical alternative for educational institutions with a fewer of students and difficulties the water supply. The selection of this solar distillation technology because the project’s location, in this case La Guajira, has a great energy potential in the use of solar radiation as a constant, renewable, and free energy source of 4.5 kilowatts per square meter on average per day. The solar distillation process is safe and easy to use, making it suitable for providing drinking water in remote regions or emergencies situations.